Modeling human color perception under extended luminance levels - Kim, Min H.; Weyrich, Tim; Kautz, Jan (ACM Transactions on Graphics, 2009)
Display technology is advancing quickly with peak luminance increasing significantly, enabling high-dynamic-range displays. However, perceptual color appearance under extended luminance levels has not been studied, mainly due to the unavailability of psychophysical data. Therefore, we conduct a psychophysical study in order to acquire appearance data for many different luminance levels (up to 16,860 cd/m 2) covering most of the dynamic range of the human visual system. These experimental data allow us to quantify human color perception under extended luminance levels, yielding a generalized color appearance model. Our proposed appearance model is efficient, accurate and invertible. It can be used to adapt the tone and color of images to different dynamic ranges for cross-media reproduction while maintaining appearance that is close to human perception. © 2009 ACM.
CRIS-Team Scopus Importer:2022-07-26
Keywords: Color appearance; Color reproduction; Psychophysics